أحاديث مادتي الشريعة وأصول الدين في المدارس الثانوية الدينية الماليزية: ‏دراسة نقدية: The Aḥādīth mentioned in Sharī’ah and Uṣūl al-Dīn Textbooks (KBD): A Critical Study - Adi Hazmi bin Mohd Rusli; Saadeldin Mansour; Khayrabadi, Mohammed Abullais (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2023)
ملخص البحث هدفت هذه الدراسة إلى التعرف بصفة أساسية على مبادئ الحوكمة في المصارف الإسلامية وتتناول هذه الدراسة الأحاديث النبوية الواردة في مادتي الشريعة وأصول الدّين، وهما من المواد الرئيسة التي تُدَرَّس تحت ما يُعرف بالمنهج الديني المتكامل (KBD)، وهو المنهج المقرر الذي يُدرس حسبه في المدارس الثانوية الدينيّة الماليزية؛ بهدف ترسيخ معرفة وفهم التلميذ لمختلف المسائل الدينية بناءً على الأدلّة الشرعية. ولذا أصبحت الكتب المدرسية لهاتين المادتين مراجع أساسية لطلبة المدارس لتعلّم الشؤون الدينيّة، وكذلك لنيل الشهادة الثانوية الماليزية (SPM). ولإدراك مدى أهميّتها، لقد تقدّم في عام 2022، أكثر من 12 ألف طالب لامتحان مادتي الشريعة وأصول الدّين لنيل شهادة الثانوية الماليزية. وبناءً على حظوتها عند المعلّمين والمتعلمّين في المدارس الماليزية، فإنها حرّية بالتنقيح والتحقيق بقصد معرفة درجة الأحاديث الواردة فيها خاصةً ما خُرّجت في غير الأمهات الست من حيث الصحة والضعف. والمنهج الذي سلكه الباحث هو المنهج الاستقرائي في جمع الأحاديث التي لم ترد في الكتب الستة التي تضمنتها الكتب المدرسيّة المتعلقة بمادتي الشريعة وأصول الدّين للصف الأول حتّى الخامس، كما استخدم الباحث المنهج النقدي في معرفة درجات الأحاديث صحّةً وضعفًا من خلال تخريجها في مصادرها وتتبّع أقوال المتقدّمين والمتأخّرين والمعاصرين من المحدّثين، ثم ترجيح ما يراه الباحث أصوب كلّما اختلف أهل العلم. وحاصل ما أوصلنا إليه تحليلنا لـ 59 حديثًا من غير الأمهات الست المذكورة في هذه الكتب المدرسيّة هو أنّ عدد الأحاديث المقبولة -من بين الصحيح والحسن لغيره- 8 أحاديث أو ما يعادل 14%، ومقدار الأحاديث المردودة -من بين الضعيف والضعيف جدا- 51 حديثًا، بما يكافئ 86%. وتفسيره أنّ عدد الأحاديث المحكوم عليها بالصحة: حديثان، حسن لذاته: حديث واحد، وحسن لغيره 5 أحاديث، والضعف الخفيف 35 حديثًا، والضعف الشديد 16 حديثًا. ABSTRACT Integrated Religious Curriculum (KBD) is a curriculum that teaches Shariah and Fundamentals of Religion among the main subjects. The curriculum is designed to educate students based on evidence on various religious issues, as well as to establish their knowledge of and understanding of these issues. In order to give students in schools an understanding of these two subjects, as well as to obtain the Malaysian Secondary Certificate (SPM), textbooks for these two subjects have become essential references. The importance of this subject was evident by the fact that, in 2022, more than 12,000 students took the Shariah and Fundamentals of Religion examination to obtain the SPM. Due to its popularity among teachers and students in Malaysian schools, it is subject to revision and investigation. This is to ensure that the hadith mentioned are authentic. During the research process, the researcher followed an inductive methodology for collecting non-six hadith collections (kutub al-sittah) mentioned in Shariah and Fundamentals of Religion textbooks for grades one to five, researcher also adopts a critical methodology for finding out whether hadith are authentic or weak by extracting their sources and examining opinions of early, late, and contemporary scholars. Any disagreement between scholars’ opinions is then resolved by the researcher favoring what he believes to be more accurate. Based on the analysis of 59 hadith that have been narrated by other than the six hadith collections (kutub al-sittah) that are mentioned in these textbooks, it has been determined that 8 hadith were accepted -whether they are sahih or Ḥasan li-dhātihi or Ḥasan li-ghayrihi-, equivalent to 14%, and 51 hadith were rejected -whether they are al-Ḍaʻīf al-Khafīf or al-Ḍaʻīf al-shadīd-, equivalent to 86%. This can be explained by the fact that the number of hadith that are confirmed to be sahih (authentic) is two hadith namely: Ḥasan li-dhātihi is one hadith, Ḥasan li-ghayrihi is five hadith, al-Ḍaʻīf al-Khafīf is 35 hadith, and al-Ḍaʻīf al-shadīd is 16 hadith.